Assessment of the implementation of succession plan and policy at MICAS - Mongi, Jamila A. (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirement for the Award of Master’s Degree of Public Administration (MPA) of Mzumbe University